Approved gene therapies in Australia: coming to a store near you. Issue 8 (16th August 2022) - Mallik, Shreyashee; Bailey, Charles G.; Rasko, John E. J.
Abstract: Gene therapy has been promising paradigm‐shifting advances in medical science for over two decades. Broadly, it is defined as a human therapy in which an existing defective gene function is added to, replaced, edited or disrupted to achieve a clinical benefit, up to and including a potential lifelong cure. Although originally set out to treat monogenic disorders, gene therapy has since been utilised to treat neoplasia, cardiovascular and neurodegenerative diseases, as well as infections. The realisation of this therapy has been dependent on the achievement of fundamental milestones in medicine, from determining the human genome sequence to identifying effective vehicles for the gene of interest, ultimately facilitating gene delivery in humans. In this review, six approved gene and cell therapies available in Australia are described. Their efficacy, adverse effects, limitations and eligibility are discussed, as well as an overview of cost and future directions.